(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to demonstrate the joint effect of overall quality management and the modified balanced scorecard in achieving the objectives of Vision 2030 In Saudi Universities (an applied study on King Khalid University for the period from 2011 to 2022) where the problem of the study focused on the low Indicators of achieving the goals of Vision 2030 AD in Saudi Universities, which may be due to the absence of the joint effect of total quality management and the modified balanced scorecard, where four hypotheses were developed and a questionnaire was designed. After collecting and analyzing data from the respondents, the study concluded that there is a joint effect of total quality management and the modified balanced scorecard in achieving the goals of Vision 2030 AD at King Khalid University, with an interlocking coefficient of (0.957). The study recommended strengthening aspects of the strengths of total quality management and the modified balanced scorecard and addressing the shortcomings that surround them at King Khalid University.